SHAPELESS DARK DIAMONDS (YAKUTITES) FROM PLACERS OF THE SIBERIAN PLATFORM AND CRITERIA OF THEIR IMPACT ORIGIN - Titkov S.V.; Gorshkov A.I.; Magazina L.O.; Sivtsov A.V.; Zakharchenko O.D. (My University, 2004)
Quite unusual shapeless dark diamonds, yakutites, which are widespread in placers in the north of the Siberian Platform, were studied by methods of analytical scanning electron microscopy and analytical transmission electron microscopy. All studied samples were found to contain inclusions of native metals, with native iron, native chromium, and Fe-Cr alloy being most abundant and particles of native gold and native lead, as well as Au-Ag, Fe-Cr-Ni, and Cu-Sn-Zn alloys, being more rare. These diamonds also contain inclusions of magnetite, ilmenite, pyrophanite, SiO2, CaCO3, halite, cotunnite, nantokite, and feldspar. The electron diffraction patterns of one of the studied samples showed lonsdaleite reflections, which represent volume ingrowths of hexagonal phase in diamond structure. The transmission electron microscopic images of yakutites showed the existence of curvilinear dislocations, dislocation loops, and misoriented microblocks, which could be formed by postgrowth plastic deformation. Most researchers believe that yakutites were derived from primary impact rocks of the Popigai ring structure. However, there are several diverse models for diamond formation in such rocks. New data on inclusions and structural defects in yakutites might count in favor of their origin as a result of endogenic explosions of ascending deep hydrocarbon fluids. However, further investigations are necessary to verify this hypothesis.